Cultural Shakespeare : essays in the Shakespeare myth - Holderness, Graham (Hatfield : University of Hertfordshire Press, 2001)
Contains essays on Shakespeare published in books and journals between 1985 and 1997.
Production (1988) -- Reproduction (1991) -- Performance (1985) -- National culture (1991) -- Heritage (1992) -- Shakespeare's England (1997) -- Bardolatry (1988) -- Shakespearean features (1991) -- Everybody's Shakespeare (1994).
Includes bibliographical references (p. [202]-206).
Keywords: Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Literature and society; English essays -- 20th century .